Atomic‐Scale Core/Shell Structure Engineering Induces Precise Tensile Strain to Boost Hydrogen Evolution Catalysis. Issue 26 (7th May 2018) - Zhu, Han; Gao, Guohua; Du, Mingliang; Zhou, Jinhui; Wang, Kai; Wu, Wenbo; Chen, Xu; Li, Yong; Ma, Piming; Dong, Weifu; Duan, Fang; Chen, Mingqing; et al.
Abstract: Tuning surface strain is a new strategy for boosting catalytic activity to achieve sustainable energy supplies; however, correlating the surface strain with catalytic performance is scarce because such mechanistic studies strongly require the capability of tailoring surface strain on catalysts as precisely as possible. Herein, a conceptual strategy of precisely tuning tensile surface strain on Co9 S8 /MoS2 core/shell nanocrystals for boosting the hydrogen evolution reaction (HER) activity by controlling the MoS2 shell numbers is demonstrated. It is found that the tensile surface strain of Co9 S8 /MoS2 core/shell nanocrystals can be precisely tuned from 3.5% to 0% by changing the MoS2 shell layer from 5L to 1L, in which the strained Co9 S8 /1L MoS2 (3.5%) exhibits the best HER performance with an overpotential of only 97 mV (10 mA cm −2 ) and a Tafel slope of 71 mV dec −1 . The density functional theory calculation reveals that the Co9 S8 /1L MoS2 core/shell nanostructure yields the lowest hydrogen adsorption energy (∆ E H ) of −1.03 eV and transition state energy barrier (∆ E 2H* ) of 0.29 eV (MoS2, ∆ E H = −0.86 eV and ∆ E 2H* = 0.49 eV), which are the key in boosting HER activity by stabilizing the HER intermediate, seizing H ions, and releasing H2 gas. Abstract : A concept of manipulating the hydrogen adsorption energy and kinetic energy barrier for transition state 2H* to boost hydrogen evolution reaction activity by creating precise tensile surface strain in Co9 S8 /MoS2 core/shell nanocrystals is demonstrated.